A crashworthiness optimisation procedure for the design of full-composite fuselage section. Issue 1 (February 2021) - Manzo, M; Perfetto, D; Caputo, F; Di Palma, L; Chiariello, A; Waimer, M
Abstract: Crashworthiness of composites is a key-point in the design of new aeronautical structures. Special attention has been addressed in the last years to the energy absorption mechanisms of dedicated components in order to limit the structural damages and to preserve the occupants' safety. Remarkable progress has been made in this field. Despite this, to further improve the design of crashworthy composite structures, components modification, sensitivity analysis, design of experiments and optimisation procedures are needed. In this work, crashworthiness improvements, related to a simplified finite element model of a full-composite fuselage section subjected to a vertical drop-test, have been introduced. The genesis of the model has been described together with its main features and details and a high-speed vertical fall has been simulated, paying attention to velocity and payload. In addition, sensitivity analyses of some components and a discussion on the main crashworthiness characteristics have been carried out. Finally, the parent fuselage section and its simplified model have been compared under both energy and deformation points of view, showing a good results agreement.